Single molecule tracking studies of the nanoscale properties of sol-gel-derived silica thin film gradients. - Cui, Chenchen (Kansas State University, 2011)
Single molecule tracking (SMT) measurements have been applied to the study of molecular mobility in sol-gel-derived silica gradient films in this thesis. Such gradient films have broad potential applications in controlled adhesion and transport of cells, vesicles and polymers; separation of complex chemical mixtures and in the development of new catalysts. Silica films were prepared by “infusion-withdrawal dip-coating”. In this method, a suitable substrate is slowly withdrawn from a silica sol of time varying composition. The deposition reservoir is initially filled with a sol derived from one silica precursor (tetramethoxysilane). A second sol, prepared from a different precursor (methyltrimethoxysilane), is then infused into the deposition reservoir, as the mixed sol is withdrawn. Films thus prepared were initially characterized by bulk fluorescence spectroscopy, infrared (IR) microscopy, contact angle goniometry, spectroscopic ellipsometry and surface profilometry. The fluorescence, IR and contact angle data all demonstrate the presence of a gradient in the methyl content of the silica film. The primary objective of the work performed under this thesis was to investigate the diffusion of Nile Red molecules in and on these films, as a function of position along the gradient, by SMT methods. Histograms of the mean-square displacement of the molecules depict the presence of at least two distinct populations: one incorporating fixed (entrapped or adsorbed) molecules and the other clearly reflecting the presence of mobile molecules. The latter population was observed to vary along the gradient dimension and also changed as the films aged over the course of five days. Molecular mobility is attributed to the presence of liquid-like silica oligomers in the films. Spatial variations in the observed mobility are tentatively assigned to variations in oligomer viscosity along the gradient. Film viscosity also changes as the polymerization of the oligomers continues during film aging.
Keywords: Single molecule tracking; Wide-field microscopy; Silica thin film gradient; Chemistry (0485)